Kick-ass business & marketing secrets how to blitz your competition - Pritchard, Bob (John Wiley & Sons, Inc., 2011)
A complete course on the rules of marketing for today's climate In this fast-paced, cluttered, and global marketplace, new influences are constantly affecting your business. Today's sophisticated consumers are searching for products that meet an emotional need, have added value, and come with no purchase risk. They want environmentally friendly products, and it's important that they buy from businesses that share their core beliefs. Despite these demands, effective marketing still comes down to knowledge, empathy, and communication. Kick Ass Business and Marketing Secrets offers a complete course on business and marketing, with simple, easily implemented rules for marketing success. The author, "Mr. Marketer" Bob Pritchard, offers expert guidance to help you thoroughly research and understand your product, market place, and competitors.-Delivers step-by-step advice on how to add value to every purchase -Details various communication vehicles and advises on how to choose the most appropriate vehicle for your campaign -Develops critical thinking skills to push you beyond your comfort level With so many new sources of market pressure, there's no room for poor marketing strategies. Get the new rules for marketing, and stand out from the rest
Includes index. - Online resource; title from digital title page (viewed on October 26, 2021)
Keywords: Marketing; Consumer behavior; Consommateurs; Comportement; marketing; BUSINESS & ECONOMICS; Distribution; BUSINESS & ECONOMICS; Marketing; General